The Impact of the Free Nutritional Meal Program (MBG) on the Learning Abilities of Junior High School Students in North Minahasa Regency - Keren Fardila Wowiling; Henry J.D. Tamboto; Allen A. Ch. Manongko; Listriyanti Palangda; Jerry Wuisan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effect of the Free Nutritious Meal Program (MBG), which includes student participation, consumption frequency, and food quality, on student learning motivation and learning ability at SMP Negeri 1 Talawaan. The study used a quantitative approach with path analysis. The study sample consisted of 102 students from three junior high schools in North Minahasa. The results showed that student participation, consumption frequency, and nutritious food quality positively influenced student learning motivation and learning ability. Learning motivation also positively influenced learning ability and acted as an intervening variable in the relationship between MBG variables and student learning ability. Thus, the MBG Program contributes to increasing student motivation and learning ability and can serve as a basis for schools and policymakers in improving the effectiveness of educational programs